Many ways to care: mobility, gender and Gauteng’s geography - Rubin, Margot; Parker, Alexandra (ORCA – Online Research at Cardiff University, 2023)
This paper builds on earlier work of geographies of care and parental care that traces the relationship between gender, parenting and mobility (Hanson 2010; Dowling 2015). Parenting is highly gendered and spatialized but we argue that the construction of what it means to be a ‘good’ mother or a ‘good’ father is a relational and relative social norm. These identities, coupled with the specifics of urban morphology, explain the daily spatial footprints of care in the Gauteng cityregion (GCR), South Africa. We examine three key elements in this paper: 1) the social and cultural norms and moral ideologies of parenthood; 2) the everyday practices of childcare; and 3) the mobility patterns and spatial footprints of parents. We argue that daily decisions that constitute the spatial footprints of caregivers are deeply entrenched in moral geographies and thus in the ideas that people have about what constitutes being a ‘good’ parent. We develop the existing literature on ‘good’ parenting, by demonstrating that these ideas are culturally and socially relative and overlain by class as well as geographic location. Spatiality, combined with ideology and identity, shape not only how we care but how we are able to care, which in turn reinforce notions of ‘good’ parenting.
Keywords: Geography of care || parenting || spatial footprints || mobility || gender || urban